Sistem Pakar Diagnosa Gejala Awal Penyakit Stroke Dengan Menggunakan Metode Fuzzy - Zahrah Zahrah; Iqbal Iqbal (Jurnal Tika, 2022)
The influence of the development of computer science has touched various fields, for example in the fields of medicine, military and others. Given the rapid development of increasingly advanced technology, especially in the field of computers, many people use computers as a tool. Also included in the medical field, computers have been included in it as a tool to do a job or identify a certain disease that facilitates human work. To determine the type of disease and how to overcome it and use the Waterfall method for system development. This expert system will also use the concept of Certainty Factor. This application is made using the PHP programming language and MySQL database as a place to store the data needed in making the application. Adobe Dreamweaver for Web design. This research produces a web-based stroke diagnosis expert system application so that it can help users to obtain the desired information. The preparation of this expert system is in the form of users and admins. Through this system, the user can identify the disease based on the symptoms that attack it. The system also has the ability to add, update, and delete features and symptoms along with the results of consultations conducted by the admin